The ABCs of Nonfinancial Defined Contribution (NDC) schemes - Robert Holzmann (Institute of Labor Economics (IZA), 2017)
Nonfinancial defined contribution (NDC) pension schemes have been successfully implemented since the mid-1990s in a number of European countries such as Italy, Latvia, Norway, Poland, and Sweden. The NDC approach features the lifelong contribution-benefit link of a financial defined contribution (FDC) personal account scheme, but is based on the pay-as-you-go format. At its start-up, the pay-as-you go commitments of the preceding defined benefit (DB) system are converted into individual personal accounts, allowing for a smooth transition from the DB to the DC format, while avoiding the very high transition costs inherent in a move from a traditional pay-as-you-go DB scheme to a fully funded FDC scheme. The NDC approach implemented by the rule book is able to manage the economic and demographic risks inherent to a pension scheme and by design creates financial sustainability. As in any pension scheme, the linchpin between financial stability and adequacy is the retirement age; in the NDC approach the individual retirement age above the minimum age is by design self-selected and by incentives should increase the effective retirement age in line with population aging. As a systemic reform approach NDC has become a strong competitor to piecemeal parametric reforms of traditional nonfinancial DB (NDB) schemes. While frequent, these reforms are far from transparent and usually too timid and too late to create financial sustainability while providing adequate pensions for the average contributor. This paper offers a largely nontechnical introduction to NDC schemes, their basic elements and advantages over NDB schemes, the key technical frontiers of the approach, and the experiences of NDC countries.
Keywords: H55; J11; J26; 330; systemic pension reform; unfunded; individual accounts; Sweden